Nilai Moral di Kabupaten Merangin dalam Proses Layanan Konseling - Mona Waroh; Adinda Eka Putri; Khairani Khofifah; Affan Yusra; Nuramita Nuramita; Zidan Alhamdika (Journal on Education, 2023)
Moral values ​​in the Merangin Regency in the process of counseling services really need to be known that there are many moral values ​​in the Merangin Regency such as the existence of traditions that contain very good moral values ​​in everyday life such as the existence of family values, togetherness, and mutual cooperation in events -events held where the event aims to connect ties between people in the environment. The method used in writing this article is the interview method, namely by asking several questions related to the title that has been taken to one of the traditional leaders in the area by telephone. With the literature study method we can read as many sources as possible related to the problem so that we can get results from summarizing the various sources we have read. In Merangin district, one of the communication media is by using traditional seloko, where traditional seloko contains advice or advice for safety and good for the Merangin people. So it can be concluded that the traditions in Merangin Regency are very diverse in terms of tradition, such as the existence of traditional seloko.